Ambiguous anti‐fouling surfaces: Facile synthesis by light‐mediated radical polymerization. Issue 2 (6th August 2015) - Pester, Christian W.; Poelma, Justin E.; Narupai, Benjaporn; Patel, Shrayesh N.; Su, Gregory M.; Mates, Thomas E.; Luo, Yingdong; Ober, Christopher K.; Hawker, Craig J.; Kramer, Edward J.
ABSTRACT: In an attempt to create a polymer brush‐based platform for the systematic study for anti‐biofouling surfaces, the benefits of surface initiated, visible light‐mediated radical polymerization are utilized to fabricate well‐defined, chemically ambiguously patterned surfaces. A variety of analytical tools are used to illustrate the precise tuning of surface chemistry and thoroughly characterize spatially well‐defined, hydrophilic/hydrophobic surfaces composed of poly(ethylene glycol methacrylate) and poly(trifluoroethyl methacrylate) with chemical definition on the micron scale. Advantages of both visible light‐mediated photopolymerization and traditional copper‐catalyzed atom transfer radical polymerization are combined to achieve both high spatial control and expanded monomer tolerance. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 253–262 Abstract : Visible light‐mediated radical polymerization allows for the fabrication of patterned diblock copolymer brushes. Surface properties of these model hydrophilic/hydrophobic ambiguous diblock brushes composed of anti‐fouling relevant monomers were thoroughly characterized, and spatial patterning gives topographically and chemically well‐defined surfaces. This strategy combines hydrophilic and hydrophobic properties on the micron length scale. Additionally, advantages of both visible light‐mediated photopolymerization and traditional copper‐catalyzed atom transfer radical polymerization were combined to achieve both high spatial definition and monomer tolerance.